Knn Search with Location and Query Solitude Using Bit Exchanging Method - Suja, K; A. Rengarajan, Dr (International Journal of Engineering and Technology, 2018)
In recent years, the need for sharing data containing user details is becoming a huge necessity. Maintaining those data becomes a complex task. In our project, we use a technique called â€œBit Exchanging Methodâ€ where the data are encrypted so that they can be protected from the adversaries. The updated records needed to be checked often so that they can be used by the encryption techniques. We use a search so called as LBS which a breakthrough concept and technology which offers us an innovative search based on the user current location. They help us to find the userâ€™s nearby pizza shop, restaurant, colleges, or any other service stations. Location based service provides the set of service which provides the geographic location of the user. Our project revolves around the HTML5 Geo Location which is an API used to find the location of the user. We utilize k closest neighbor questions where the portable client inquiries the area based specialist organization about surmised k closest purposes of enthusiasm on the premise of his present area. The installing of situating abilities in cell phones encourages the development of area based administrations which is considered as the following "executioner application" in the remote information advertise. Compared with our existing work, our solutions are efficient and provide secured privacy. Examinations have demonstrated that our answer is proper for KNN inquiries.Â Â